Expression of hOvol2 in the XY body of human spermatocytes. (2nd May 2016) - Taniguchi, H.; Katano, T.; Nishida, K.; Yao, I.; Morimoto, Y.; Matsuda, T.; Ito, S.
Summary: Male infertility is common at infertile clinics, and 10–20% of infertile males are azoospermic. Non‐obstructive azoospermia is a complex multifactorial disease, and the process of spermatogenesis remains largely unknown. Ovol1 and Ovol2, a family of zinc finger transcription factors, are expressed in spermatocytes at the pachytene stage and are suggested to be critical regulators of pachytene progression in male germ cells. In this study, we examined the expression of human Ovol2 (hOvol2) in the seminiferous tubes of patients subjected to testicular sperm extraction. We first cloned hOvol1 and hOvol2 from the testis of one of the patients and found no alteration in these nucleotide sequences of this patient. While hOvol1 and hOvol2 were detected by RT‐PCR in the testis of patients capable of spermatogenesis, they were not detected in those with Sertoli cell‐only syndrome. We recently succeeded in preparing anti‐Ovol2 antibody by immunising rats with recombinant mouse Ovol2 (mOvol2) and confirmed the specificity and cross‐reactivity of this antibody with hOvol2 in cells transfected with hOvol1 or hOvol2 cDNA. hOvol2 expression was restricted to the XY body of spermatocytes at the pachytene stage. This study demonstrates that hOvol2 is expressed in germ cells and may be involved in spermatogenesis.